Profit efficiency among Islamic banks in Malaysia - Syazana An-Aqilah, Abdul Manaf (2018)
The sustainability of banking system depends on the profit efficiency of banking system. Profit efficiency of lslamic banks in Malaysia shows a fluctuating trend from the period of 2012 to 2016. The purpose of this study is to analyse the post Global Financing Crises (GFC) period and to examine the impact of external and internal factors on the profit efficiency of lslamic banks in Malaysia covering the period 2012 to 2016. In this study profit efficiency is measured using net income (NI). Secondary data was used from 16 Islamic banks in Malaysia for Observation 80. There are two external factors which are Gross Domestic Product (GDP) and Inflation (INF) and five internal factors which are Loan Growth (LGROW), Impaired Financing (IF), Loan Loss Provision (LLP), Net Interest Margin (NIM) and Staff Efficiency (STAFFX) tested in this study. This study used panel data analysis to analyse the data obtained from Fitch Connect Database. The study found that, factors like INF and STAFFX have negative significant impact on NI while NIM have a positive and significant impact on NI of Islamic banks in Malaysia. The other four factors which are GDP, LGROW, LLP and IF are found to be insignificant towards NI of Islamic banks in Malaysia. This study is beneficial for researches as guidance in making a good research. On the other hand, it is also important for the Islamic banks management team, investors as well as depositors for the purpose of gaining a greater understanding on the performance of the banks.